Europe's quest for monetary stability: central banking gone astray - Jörg Bibow (Levy Economics Institute of Bard College, 2005)
This paper provides an overview of central banking arrangements in those European countries that have adopted the euro. Issues addressed include the structure of the Eurosystem and its central banking functions, the kind of independence granted to the system and the role of monetary policy that central bankers have adopted for themselves, the two-pillar policy framework, operating procedures, and actual performance since the euro's launch in 1999. The analysis concludes that, given the current macroeconomic policy regime, trends, and practices, the euro is on track for failure.
Keywords: E42; E58; E61; E65; 330; Central banking; monetary policy; European Central Bank; Eurosystem; central bank independence; policy strategy; operating procedure